Evaluation Report on the Village Sanitation Scheme of the Gandhi Smarak Nidhi in Maharashtra - Planning Commission (Planning Commission, 1972)
One of the four-fold activities of the Gandhi Smarak Nidhi was the village sanitation or 'Bhangi Mukti Scheme' which aimed at constructing the latrines free from the services of the sweepers, providing privacy particularly to the women-folk, utilizing night-soil for producing manure, and improving the village sanitation and hygiene. This programme gained momentum in Maharashtra State during the Gandhi Centenary year - 1969-70 and by the end of 1970, over 21, 000 latrines were constructed. The Programme Evaluation Organization conducted the study during the year 1970-71 with a view to examine the operation of the scheme and the extent of adoption, experience and reaction of the adopters including the factors associated with the acceptance or otherwise of the programme, and the general impact of the scheme.
Programme Evaluation Organisation Planning Commission Government of India